Social Stigma toward Health Workers Associated with Coronavirus Disease 2019 - Faris, Muhammad; Arifianto, Muhammad Reza (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The World Health Organization declared the novel coronavirus disease 2019 (COVID-19) a global pandemic, which classifies the outbreak as an international emergency. This disease has been confirmed as the first pandemic in 21st century. Healthcare workers on the front line who are directly involved in the diagnosis, treatment, and care of patients with COVID-19 are at risk of being stigmatized. AIM: This study was a review. METHODS: This study was conducted by conducting analytic appraisal using published journals and sources through an electronic database. RESULTS: From cases in Indonesia and other countries, there’s bunch of examples that healthcare workers being negatively stigmatized in case of COVID-19. They lost their rights to have a normal life in this pandemic era. DISCUSSION: The government itself has actually promoted socialization about COVID-19, including the importance of mutual support and assistance including morally and psychosocially for the sufferers and health workers involved. However, negative stigma for health workers and patients and their families suffering from COVID-19 remains strongly attached until nowadays. Synergy between the central government, regional governments, community leaders, and referral hospital officials are certainly important to overcome this stigma problem, in addition to promoting education in the community. CONCLUSION: Synergy among the central government, regional governments, community leaders, and referral hospital officials is certainly important to overcome this stigma problem, in addition to promoting education in the communit